2012
DOI: 10.1089/nat.2012.0359
|View full text |Cite
|
Sign up to set email alerts
|

Small Interfering RNA Targeting the Nonstructural Gene 1 Transcript Inhibits Influenza A Virus Replication in Experimental Mice

Abstract: Nonstructural protein 1 (NS1) of influenza A viruses counteracts the host immune response against the influenza viruses by not only inhibiting the nuclear export and maturation of host cell messenger RNA (mRNA), but by also blocking the double-stranded RNA-activated protein kinase-mediated inhibition of viral RNA translation. Reduction of NS1 gene product in the host cell may be a potent antiviral strategy to provide protection against the influenza virus infection. We used small interfering RNAs (siRNAs) synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Other factors that may explain differential duck and chicken responses to influenza include viral modification of the immune system such as by influenza NS1 which blocks key cellular protective mechanisms (Rajput et al, 2012). In particular, NS1 interacts with the RIG-like helicases further suggesting the importance of RIG-I for protecting influenza-infected organisms (Rückle et al, 2012).…”
Section: Figmentioning
confidence: 99%
“…Other factors that may explain differential duck and chicken responses to influenza include viral modification of the immune system such as by influenza NS1 which blocks key cellular protective mechanisms (Rajput et al, 2012). In particular, NS1 interacts with the RIG-like helicases further suggesting the importance of RIG-I for protecting influenza-infected organisms (Rückle et al, 2012).…”
Section: Figmentioning
confidence: 99%
“…Rajput et al observed a 60% inhibition of NS1 RNA with either of two NS1-specific siRNAs in co-transfection experiments using an NS1 expression construct in MDCK cells (Rajput et al, 2012). Remarkably, intravenous administration of increasing doses of NS1-specific siRNA in BALB/c mice challenged with 2×10 6 p.f.u.…”
Section: Nucleic Acid-based Ns1 Inhibitorsmentioning
confidence: 99%
“…88 Furthermore, Rajput et al reported that when NS1-specific siRNA was administered in experimental mice, a 92% reduction was observed in the levels of NS1 gene expression in the lungs. 98 Significant decrease in cytokine levels and virus titers in the lungs were also observed. Zhou et al also designed three siRNAs against the NP, PB1 and PA proteins of H5N1 avian influenza virus.…”
Section: Possibility Of Use As Anti-influenza Agent In Human and Animalsmentioning
confidence: 87%